Prevalence and Predictors for Depression among Medical Students during Coronavirus Disease-19 Pandemic: A Cross-sectional Study - Esmat, Shereen; Attia, Abeer; Elhabashi, Eman (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Since the declaration of the World Health Organization of the coronavirus (SARS-COV-2) as a pandemic, several countries have locked down and quarantined their residents with restrictive procedures to control spread of the disease. Due to pandemic related stressors, concerns and worries have developed regarding negative psychological impact on the mental well-being of the general population, particularly those known to have higher levels of psychological impairment with high vulnerability to mental health diseases such as medical students. AIM: The objectives of the study were to assess the prevalence of self-reported depression and to explore its predictors during the period of Coronavirus Disease 2019 first lock down among medical students. METHODS: This was a cross-sectional study design. The study was conducted at Kasr Alainy Medical School, Faculty of Medicine, Cairo University, Egypt, in June 2020. A simple random sample was picked of one subgroup of 4th year medical students (No. = 300) at faculty of medicine during the academic year 2019–2020. Self-administered questionnaires including Beck’s Depression Inventory scoring were distributed using Google form through communication social media such as WhatsApp. RESULTS: Out of the 300 participants, 238 responses were received with response rate 79.3%. Results indicated that 38.2% of the respondents were experiencing depression with different degrees with Beck’s Depression Inventory mean scores was 19.4 ± 11.6. Multiple logistic regression analysis point out that gender (odds ratio [OR] = 2.4 and p = 0.022) and “Good” grade level of academic performance (OR = 7.2 and p = 0.045) are significant predictors for developing depression among the participating medical students. CONCLUSION: A significantly high prevalence of depression is detected among medical students during the first wave of the SARS-COV-2 pandemic. The prevalence of depression is more among females than males and more with medical students achieving “Good” grade level.